New Numerical Methods for Solving Differential Equations - Ababneh, Osama. Y. (JOURNAL OF ADVANCES IN MATHEMATICS, 2019)
In this paper, we present new numerical methods to solve ordinary differential equations in both linear and nonlinear cases. we apply Daftardar-Gejji technique on theta-method to derive anew family of numerical method. It is shown that the method may be formulated in an equivalent way as a RungeKutta method. The stability of the methods is analyzed.